Novel Interleukin-10 Gene Polymorphism Is Linked to Gestational Diabetes in Taiwanese Population - Kang, Jessica; Liu, Chia-Hsiung; Lee, Chien-Nan; Li, Hung-Yuan; Yang, Chien-Wen; Huang, Shu-Chien; Lin, Shin-Yu; Jou, Tzuu-Shuh (Frontiers in Genetics, 2019)
Objective: The association of interleukin-10 (IL-10) polymorphism with diabetes and its complication was recently established, while there were few researches considering the potential role of IL-10 in gestational diabetes (GDM). This study aimed to investigate the association between IL-10 gene rs1800896 (-1082 A/G), rs1800871 (-819 T/C), rs1800872 (-592 A/C) and rs3021094 (3388 A/C) single nucleotide polymorphisms (SNPs) and GDM susceptibility. Methods: This study included 72 GDM patients and 100 healthy pregnant women. Direct sequencing of the products from polymerase chain reactions of the extracted genomic DNA from study subjects were conducted for analyzing IL-10 gene polymorphism and further genotype frequencies were compared. Plasma IL-10 concentration was measured by ELISA method. Results: The results revealed no significant difference in -592 A/C, -819 T/C and -1082 A/G genotypes. Significantly increased prevalence of A allele (P = 0.028, OR = 1.69, 95% CI = 1.081-2.64) and A/A genotype (P = 0.031, OR = 2.881, 95% CI = 1.145-7.250) at a previously un-characterized rs3021094 SNP were discovered in the GDM group. Increased IL-10 levels and insulin resistance were also related to the genotype of rs3021094. The risk of GDM was increased when IL-10 level was over 6.5 pg/ml. Conclusions: Our study demonstrated that A allele and A/A genotype of rs3021094 SNP in IL-10 gene were linked to increased risk for GDM, IL-10 plasma level and insulin resistance, which could be potential targets for early screening and detection of GDM.